2015
DOI: 10.1007/s12630-015-0315-1
|View full text |Cite
|
Sign up to set email alerts
|

Combined general and neuraxial anesthesia versus general anesthesia: a population-based cohort study

Abstract: Purpose To determine whether combining spinal or epidural anesthesia with general anesthesia (combined anesthesia) reduces major medical complications of elective surgery compared with general anesthesia alone. Methods We conducted a propensity-matched population-based historical cohort study using large healthcare databases from Ontario, Canada. We identified patients undergoing 21 different elective procedures that were amenable to either combined anesthesia or general anesthesia alone in 108 hospitals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
0
14
0
2
Order By: Relevance
“…66 A recent populationbased historical cohort study found combined general and neuraxial anaesthesia to have a similar incidence of AKI when compared with general anaesthesia alone. 67…”
Section: Anaesthesiamentioning
confidence: 99%
“…66 A recent populationbased historical cohort study found combined general and neuraxial anaesthesia to have a similar incidence of AKI when compared with general anaesthesia alone. 67…”
Section: Anaesthesiamentioning
confidence: 99%
“…Previous work suggests that neuraxial anesthesia is not protective for cardiovascular outcomes. 23 None of the defined secondary outcomes of POISE-2 differed significantly between groups at 1 yr. The tertiary outcome of congestive heart failure was increased at the 1-yr follow-up in patients randomized to clonidine (hazard ratio = 1.54; 95% CI, 1.10 to 2.15, P = 0.012).…”
Section: Perioperative Medicinementioning
confidence: 86%
“…В когортном исследовании, проведенном D. Nash, R. Mustafa, E. McArthur и соавт. [46], было выявлено, что сочетание общей анестезии с нейроаксиальной сопровождается аналогичной по сравнению только с общей анестезией частотой ОПП.…”
Section: интраоперационное ведениеunclassified